Book public pages in Instagram - T. D. Rubanova (Библиосфера, 2020)
The peculiarity of the Russian-language Instagram segment is that for many users it has become the platform for text self-expression and discussions (including on reading issues). This explains the fact that many publishers and bookstores create their own Instagram accounts to promote book products. The purpose of the article is to identify the marketing potential of book public pages in Instagram. The author sets the following tasks: to identify successful practices of publishers and bookselling organizations in Instagram; analyze them from the point of view of text content, visual design; identify the main forms of users engagement; calculate the engagement rate (ER); identify possible "recipes" for the success of book public pages. Viewing the official websites of publishers and bookstores allowed the identification of book public posts with a significant number of subscribers and that of forms to attract users, and the determination of content features and visual design. A comparison of the activity level of public pages: @ eksmolive and @mifbooks of two major publishing houses. For this purpose, the number of posts, likes and comments for the period from 23.10.2019 to 22.11.2019 was calculated, as well as the engagement rate using the ER method. The author comes to the conclusion that the Instagram is widely used by publishing organizations and booksellers as a promising platform for book promotion and reading support, active exchange of information with the audience, increasing people’s loyalty, brand promotion, organization of direct sales. Effectiveness of the presence of booksellers in Instagram largely depends on the competent segmentation of the audience, the uniqueness of the content and visual design, and the use of various techniques and methods to enhance user engagement.